Adaptive Capabilities of Underweight Newborns and Development Features in their First Year of Life - Kh. Akramova1, A. Djalilov2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: The issue of caring underweight infants is vital today because of the relatively high mortalityrate. The perinatal death in full-term babies born with low birth weight is 3–8 times higher than in childrenwith normal weight and takes the second place in the structure of perinatal mortality after prematurity.Moreover, the lack of a well-established concept for the management of such children in the first year oflife in the literature, make us to conduct additional studies in this sphere. In order to evaluate the adaptivecapabilities of children and monitor their physical development, growth curves and development of childrenchecked according to WHO standards.Method: 281 newborns and 272 mothers were examined. Newborns were divided into 2 groups: group1-83 premature infants with low body weight; group 2-103 full-term newborns with low body weight. Thecontrol group consisted of 95 full-term newborns. Quantitative determination of human placental growthfactor (PlGF) was performed based on the enzyme-linked immunosorbent assay. Correlation analysis andstatistical processing of the gained data were calculated on MS Excel - XP software and statistical analysisof the results was carried out using method of variation statistics.Results. 83 mothers had babies born prematurely with low body weight relative to gestational age (group 1);in 102 mothers - full-term, but with low body weight (group 2). The control group consisted of 87 womenwhose newborns were born on time (38.4 ± 6.3 weeks) and body weight corresponded to gestational age.A high risk of birth with low body weight in pregnant women was observed with signs of fetal growthretardation by ultrasound examination (OR = 11.58), with anemia (OR = 8.17), other malnutrition (OR =5.75), placental insufficiency (OR = 5.46). Signs of perinatal cerebral hypoxic-ischemia of the 2nd degreewere noted in groups 1 and 2, respectively, in 73.5% and 66.0% of children.Conclusion: Pregnant women who have proteinuria and preeclampsia are 3 times more likely to havebabies with low body weight compared to pregnant women with normal renal function and blood pressure.Underweight preterm infants are born in severe asphyxia, with a severe degree of RDS, severe disordersof the central nervous system; they require primary resuscitation measures more often, longer antibacterialtherapy.